2021
DOI: 10.1002/pros.24226
|View full text |Cite
|
Sign up to set email alerts
|

Pathological significance and prognostic role of LATS2 in prostate cancer

Abstract: Background Large tumor suppressor 2 (LATS2) is an important regulator of the Hippo pathway and it plays crucial roles in cell survival and behaviors. Herein, we evaluated the pathological roles of LATS2 in prostate cancer (PC), for which very little information is available. Methods Cell proliferation, migration, and invasion in response to the siRNA‐mediated knockdown (KD) LATS2 expression were evaluated in two PC cell lines (LNCaP and PC3). The expression of LATS2 in specimens from 204 PC patients was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Phosphorylation of YAP1 by LATS2 inhibits its translocation into the nucleus to regulate cellular genes important for cell proliferation, cell death, and cell migration, and plays a critical role in genomic stability (33). Moreover, a recent study has demonstrated that LATS2 is a potential therapeutic target as a predictor for outcome in patients with PC (34). DDX3X is a member of the large DEAD-box protein family and functions as a tumor suppressor.…”
Section: Comparative Analysis Of Genomic Profiles In Tumor Samplesmentioning
confidence: 99%
“…Phosphorylation of YAP1 by LATS2 inhibits its translocation into the nucleus to regulate cellular genes important for cell proliferation, cell death, and cell migration, and plays a critical role in genomic stability (33). Moreover, a recent study has demonstrated that LATS2 is a potential therapeutic target as a predictor for outcome in patients with PC (34). DDX3X is a member of the large DEAD-box protein family and functions as a tumor suppressor.…”
Section: Comparative Analysis Of Genomic Profiles In Tumor Samplesmentioning
confidence: 99%
“…PDE5 inhibitors restore nitric oxide (Kalsi et al, 2005;Lee et al, 2022) and are selective vasodilators of the NO-cGMP signaling pathway (Aversa et al, 2019;Ahmed et al, 2021). PDE5 inhibitors have been shown to benefit vasculature oxygenation (Morelli et al, 2011;Michel et al, 2015), prevent ischemia-hypoxia (Saito et al, 2014;Zarifpour et al, 2015;Fujii et al, 2019), and reduce microvascular/endothelial dysfunction (Cellek et al, 2014;Ölmestig et al, 2020;Statsenko and Urologiia, 2021); they also reduce oxidative stress (Matsuo et al, 2020), inflammation (Vignozzi et al, 2013;Peixoto and Gomes, 2015), amyloids (Kang et al, 2022), and prostate weight (Kobayashi et al, 2022).…”
Section: Nitric Oxide Bioavailability and Expression Signalingmentioning
confidence: 99%